Terms of Pre-trial Investigation of Criminal Misdemeanors: Gaps in Legislation and Case Law - Opolska, Natalia (Teisė, 2022)
The purpose of the article is to analyze the positive judicial practice that has developed in the field of applying the terms of pre-trial investigation of criminal misdemeanors, highlight gaps in legislation, as well as develop proposals for improving the current Criminal Procedure Code of Ukraine.